MN1 Neurodevelopmental Disease-Atypical Phenotype Due to a Novel Frameshift Variant in the MN1 Gene - Tian, Qi; Shu, Li; Zhang, Pu; Zeng, Ting; Cao, Yang; Xi, Hui; Peng, Ying; Wang, Yaqin; Mao, Xiao; Wang, Hua (Frontiers in Molecular Neuroscience, 2021)
Background MN1 C-terminal truncation (MCTT) syndrome was caused by variants in C-terminal region of MN1 in 2020. The clinical features of MCTT syndrome includes severe neurodevelopmental abnormalities and brain abnormalities. We firstly reported patient carried MN1 variant in C-terminal region with mild developmental delay and normal brain MRI. Methods Detailed clinical information was collected in the pedigree. The Whole-exome sequencing (WES) accompanied with Sanger sequencing validation were performed. Functional study based on HEK239T cells were performed. Results A de novo heterozygous c.3734delT: p.L1245fs variant were detected. HEK239T cells transinfected with the de novo variant showed decreased proliferation, enhanced apoptotic rate and MN1 nuclear aggregation. Conclusion Our study expended the clinical and genetic spectrum of MCTT which contribute to the genetic counseling of MN1 gene.